Human resource development and liberalisation policy: A study of rural employment programmes in India - Ramulu, Ch. Bala (1996)
After highlighting importance of HRD and the action programme being pursued in the country through various rural employment programmes to develop this human resource, the author evaluates the outcome of these programmes by presenting findings of an empirical study conducted in Andhra Pradesh. He then discusses the implications of the distortions being caused by adoption of liberalisation programmes for HRD effort in future. - Reproduced
Keywords: Manpower policy - India; Employment, Rural - India; Employment